PERKEMBANGAN PGRI MULAI DARI MASA KOLONIAL HINGGA MASA SEKARANG - Agil Budi Prayogo (JUSAN: Jurnal Sejarah Peradaban Islam Indonesia, 2024)
Education at the beginning of Indonesia's independence was an important aspect to foster the spirit of fighting for nationalism and the ideals of independence for the Republic of Indonesia. The attention of the new Indonesian government and some of the revolutionary figures who are aware that the field of education is very important to foster a spirit of nationalism and efforts to instill awareness as an independent nation. Based on the principles of new education and teaching, the Teaching Research Committee formulated the goals and foundations of education and the school system that characterizes Indonesia. The Republic of Indonesia Teachers Association Organization, as a forum for Indonesian teachers since the Dutch East Indies era. Since the proclamation, the PGRI organization has established itself as a fighting organization that helps defend the independence and sovereignty of Indonesia, the Republic of Indonesia. This organization is a manifestation of Indonesian teachers in taking part and responsibility in accordance with their professional field as educators to fulfill the independence they aspire to. Therefore, this organization is seen as unifying teachers who are: 1) unitary, 2) independent, 3) non-political parties. It is also a means, a vehicle for the interests of teachers for the development of their profession, education in general and their service to the homeland and nation. Keywords: History of education; Nationalism; Indonesian Revolution; PGRI